Research Topic: Evaluating the Venture Capital Growth, Impediments, and Prospects in Sub-Saharan Africa Nations - Ahmed Idi Kato (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
Purpose: Nowadays, is it internationally acknowledged that access to venture capital (VC) investment is central for market internationalisation, entrepreneurship development, job creation and economic growth. Although VC’s reputation is universally accepted among scholars and in academic literature, there is still a knowledge gap in Africa. The study intended mainly to explore why developing nations in Africa have not been fruitful at stimulating early-venture capital investment compared to the developed nations. We reflect a range of probable reasons that impede both foreign and domestic VC investment, including difficulties faced by the entrepreneurs in obtaining funding from VC firms. Design/methodology/approach: Using multiple regression analysis, we examined data from 61 VC companies’ resident in East and Southern Africa from 2015-2021, coupled with in-depth interviews with twelve VC investors. Findings: The study revealed that several early-stage firms lack the capacity to manage large tickets of above US$5 million. Second, the results affirm that the absorptive capacity and VCs’ geographical preference all combined significantly influence the growth of the VC industry, and this problem is heightened by government’s limited support to creating supportive policies that enhance SMEs’ growth. Practical implications: The study offers good insights by suggesting direct government intervention in the form of instituting tax incentives on capital gains to inspire more foreign investors. Paper type: Research paper